DOMINASI CERAI GUGAT DI PENGADILAN AGAMA KABUPATEN SIDRAP (Polemik dan isu Gender dalam Kasus Perceraian di PA Sidrap) - H. Sudirman L. (DIKTUM: Jurnal Syariah dan Hukum, 2013)
The number of divorce that occurred in the district increased Sidrap based on data from the Religious Court Sidrap in 2013 recorded 708 divorce cases filed with the Court of Religion, 80.5% were contested divorce. This condition is developing new polemic in the life of society and raises new issues related to gender issues. Issues arising start growing awareness of women of their rights in a marriage that demands sameness and equality. Gender issues was often misunderstood issue, as if it was a form of resistance to women, when in fact the concept of gender is socially constructed between women and men that accommodates the problems and issues them to seek justice and equality.